Pengaruh Dukungan Sosial terhadap Prokrastinasi Siswa yang Bermukim di Pesantren Madrasah - Firda Laily Novia Candra Waty; Mirna Wahyu Agustina (Happiness: Journal of Psychology and Islamic Science, 2022)
Islamic boarding schools teach independence and discipline to students. But in fact students have not been able to regulated themselves properly which causes students to do academic procrastination, so there needs to be more social support from the surrounding enviroment. This study aims to determine the effect of social support on the academic procrastination of students living in Islamic boarding schools at MTs N 3 Bojonegoro. This type of research is quantitative causal comparative. The sample used in this study were 48 respondents. The data collection method in this study used the social support scale and the academic procrastination scale. Hypothesis testing using a simple regression test, the results obtained a significance value of 0,002<0,05. With a regression coefficient value of -0,612 and  value of 0,185, it is equal to 18,5%. The result of this study can be said that the social support has a significant effect on the academic procrastination of students living in Islamic boarding schools at MTs N 3 Bojonegoro. The negative value on the regression coefficient can be said that these two variables have a negative influence, it means that the higher the social support, the lower the student’s academic procrastination.